Synopsis on the elucidation of legal maxims in Islamic law - Zaydan, 'Abd al-Karim (IBFIM, 2015)
Legal maxims or al-Qawa'id are designed to facilitate a better understanding of Shari'ah or Islamic Law. They are theoretical abstractions that are typically in the form of short epithetical and expressive statements or wise sayings of Shari'ah goals and objectives, and their development are parallel with the study and theory of law or fiqh. As such, al-Qawa'id enjoys an important place in Islamic jurisprudence as they encapsulate concepts and precepts that can help one understand the details of the Islamic Law as it stands and also help one to arrive at the appropriate ruling where no explicit law exist. The translation of this book is made available to assist students and professionals in the subject of al-qawa'id al-Fiqhiyyah that is also relevant to the field of Islamic banking and finance. In addition, it is to encourage further deliberation and discussion as it is a necessity to understand their meanings and implications in order to establish good governance.